Forskolin induces FXR expression and enhances maturation of iPSC-derived hepatocyte-like cells - Loerch, Christiane; Szepanowski, Leon-Phillip; Reiss, Julian; Adjaye, James; Graffmann, Nina (Frontiers in Cell and Developmental Biology, 2024)
The generation of iPSC-derived hepatocyte-like cells (HLCs) is a powerful tool for studying liver diseases, their therapy as well as drug development. iPSC-derived disease models benefit from their diverse origin of patients, enabling the study of disease-associated mutations and, when considering more than one iPSC line to reflect a more diverse genetic background compared to immortalized cell lines. Unfortunately, the use of iPSC-derived HLCs is limited due to their lack of maturity and a rather fetal phenotype. Commercial kits and complicated 3D-protocols are cost-and time-intensive and hardly usable for smaller working groups. In this study, we optimized our previously published protocol by fine-tuning the initial cell number, exchanging antibiotics and basal medium composition and introducing the small molecule forskolin during the HLC maturation step. We thereby contribute to the liver research field by providing a simple, cost-and time-effective 2D differentiation protocol. We generate functional HLCs with significantly increased HLC hallmark gene (ALB, HNF4, and CYP3A4) and protein (ALB) expression, as well as significantly elevated inducible CYP3A4 activity.